Activated platelets are the source of elevated levels of soluble CD40 ligand in the circulation of inflammatory bowel disease patients. Issue 10 (11th September 2003) - Danese, S; Katz, J A; Saibeni, S; Papa, A; Gasbarrini, A; Vecchi, M; Fiocchi, C
Abstract : Background: The CD40/CD40L system, a key regulator and amplifier of immune reactivity, is activated in inflammatory bowel disease (IBD) mucosa. Aims: To determine whether plasma levels of sCD40L are elevated in Crohn's disease (CD) and ulcerative colitis (UC) patients compared with normal controls, to investigate the cellular source of sCD40L, and to explore CD40L induction mechanisms. Patients: CD, UC, and normal control subjects were studied. Methods: The concentration of sCD40L in plasma and supernatants of freshly isolated platelets and autologous peripheral blood T cells (PBT) was measured by ELISA. Surface CD40L expression level was measured by flow cytometry in resting and thrombin activated platelets, and unstimulated and CD3/CD28 stimulated PBT before and after coculture with human intestinal microvascular endothelial cells (HIMEC). Results: Compared with normal controls, plasma sCD40L levels were significantly higher in both CD and UC patients and proportional to the extent of mucosal inflammation. Platelets from IBD patients displayed a significantly higher surface CD40L expression than those from control subjects, and released greater amounts of sCD40L than autologous PBT. Contact with IL-1β activated HIMEC induced significant upregulation of CD40L surface expression and release by platelets. Conclusions: Elevated levels of sCD40L in the circulation of IBD patients reflect enhanced surface expression and release of CD40L by platelets. This phenomenon translates to an increased platelet activation state apparently induced by passage through an inflamed mucosal microvascular bed, a conclusion supported by the positive correlation of plasma sCD40L levels with the extent of anatomical involvement by IBD. These results suggest that platelet-endothelial interactions critically contribute to activation of the CD40 pathway in IBD.